In Situ Iodide Passivation Toward Efficient CsPbI3 Perovskite Quantum Dot Solar Cells - Shi, Junwei; Cohen‑Kleinstein, Ben; Zhang, Xuliang; Zhao, Chenyu; Zhang, Yong; Ling, Xufeng; Guo, Junjun; Ko, Doo‑Hyun; Xu, Baomin; Yuan, Jianyu; Ma, Wanli (Nano-Micro Letters, 2023)
All-inorganic CsPbI3 quantum dots (QDs) have demonstrated promising potential in photovoltaic (PV) applications. However, these colloidal perovskites are vulnerable to the deterioration of surface trap states, leading to a degradation in efficiency and stability. To address these issues, a facile yet effective strategy of introducing hydroiodic acid (HI) into the synthesis procedure is established to achieve high-quality QDs and devices. Through an in-depth experimental analysis, the introduction of HI was found to convert PbI2 into highly coordinated [PbIm]2−m, enabling control of the nucleation numbers and growth kinetics. Combined optical and structural investigations illustrate that such a synthesis technique is beneficial for achieving enhanced crystallinity and a reduced density of crystallographic defects. Finally, the effect of HI is further reflected on the PV performance. The optimal device demonstrated a significantly improved power conversion efficiency of 15.72% along with enhanced storage stability. This technique illuminates a novel and simple methodology to regulate the formed species during synthesis, shedding light on further understanding solar cell performance, and aiding the design of future novel synthesis protocols for high-performance optoelectronic devices. Highlights: 1 The introduction of hydroiodic acid (HI) manipulates the dynamic conversion of PbI2 into highly coordinated species to optimize the nucleation and growth kinetics. 2 The addition of HI enables the fabrication of CsPbI3 perovskite quantum dots with reduced defect density, enhanced crystallinity, higher phase purity, and near-unity photoluminescence quantum yield. 3 The efficiency of CsPbI3 perovskite quantum dot solar cells was enhanced from 14.07% to 15.72% together with enhanced storage stability.